2021
DOI: 10.3389/fendo.2021.666595
|View full text |Cite
|
Sign up to set email alerts
|

Free Thyroxine Levels are Associated with Cold Induced Thermogenesis in Healthy Euthyroid Individuals

Abstract: Thyroid hormone (TH) is an important regulator of mammalian metabolism and facilitates cold induced thermogenesis (CIT) in brown adipose tissue (BAT). Profound hypothyroidism or hyperthyroidism lead to alterations in BAT function and CIT. In euthyroid humans the inter-individual variation of thyroid hormones is relatively large. Therefore, we investigated whether levels of free thyroxine (T4) or free triiodothyronine (T3) are positively associated with CIT in euthyroid individuals. We performed an observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a recent study by Maushart et al, BAT activity assessed by 18F-FDG uptake in PET-CT after cold exposure was related to levels of free T4 (fT4). It was shown that cold-induced thermogenesis was approximately fourfold higher in subjects in the highest tertile of fT4 when compared to the lowest tertile of fT4 [36].…”
Section: Thermogenesismentioning
confidence: 98%
“…In a recent study by Maushart et al, BAT activity assessed by 18F-FDG uptake in PET-CT after cold exposure was related to levels of free T4 (fT4). It was shown that cold-induced thermogenesis was approximately fourfold higher in subjects in the highest tertile of fT4 when compared to the lowest tertile of fT4 [36].…”
Section: Thermogenesismentioning
confidence: 98%
“…Higher serum T3 levels were found in cold-induced 18 FDG BAT–positive individuals in one study ( 406 ) and with lower BAT fat fraction on MRI in another ( 408 ). A positive association between serum free T4 levels and cold-induced BAT glucose uptake was found in 24 euthyroid and healthy participants ( 409 ). However, another large cross-sectional study did not find any association between serum thyroid hormone levels and cold-induced BAT glucose uptake in 106 healthy individuals ( 407 ).…”
Section: Regulation Of Brown Adipose Tissue Activity and Capacitymentioning
confidence: 99%
“…In a study by Law et al, where 2 groups of young women were compared—1 group with autoimmune primary hypothyroidism and a control group—it was demonstrated that patients exhibited differences in temperature in a resting state as well as in a cold-induced thermogenesis state [ 26 ]. Another study in healthy euthyroid patients indicated a correlation between cold-induced thermogenesis control and FT4 levels, suggesting that variations in thyroid hormone levels within the euthyroid range are related to the capability to adapt to cool temperatures and affect energy balance [ 27 ]. These findings imply that, even with controlled hypothyroidism, thermoregulation alterations may occur.…”
Section: Discussionmentioning
confidence: 99%